2012
DOI: 10.1111/j.1471-4159.2011.07630.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in microglial colonization of the developing rat brain

Abstract: Microglia are the resident immune cells within the brain and their production of immune molecules such as cytokines and chemokines is critical for the processes of normal brain development including neurogenesis, axonal migration, synapse formation, and programmed cell death. Notably, sex differences exist in many of these processes throughout brain development; however, it is unknown whether a sex difference concurrently exists in the colonization, number, or morphology of microglia within the developing brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

65
590
9
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 577 publications
(667 citation statements)
references
References 52 publications
65
590
9
3
Order By: Relevance
“…Studies in rodents suggested a higher number of microglia and astrocytes in adult females (36,37), so we cannot exclude the possibility that a higher prevalence of women in the MS group may have contributed to the higher 18 F-PBR111 V T in patients.…”
Section: Discussionmentioning
confidence: 92%
“…Studies in rodents suggested a higher number of microglia and astrocytes in adult females (36,37), so we cannot exclude the possibility that a higher prevalence of women in the MS group may have contributed to the higher 18 F-PBR111 V T in patients.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, as different areas of the brain develop at different time points in the neonatal period, this may result in different long term effects, depending upon the time of inflammation. Even the immune competent microglia in the brain appear at different times in different structures; for example the hypothalamus and the hippocampus vary significantly in microglia number in early development (Schwarz et al, 2012).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Certainly, microglia are emerging as a key regulator of CNS development and in particular, evidence is building that sex differences in microglia during early postnatal life may contribute to long-term sex differences in brain function. [36][37][38] Microglia numbers are increased in the early postnatal period, compared to adolescence and adulthood, with peak numbers occurring in the second week of postnatal life with a gradual reduction in number in the following weeks [39] . The morphology of microglia in the first postnatal week in rodents is consistent with activated ameboid microglia found in the adult CNS [24,38,39] .…”
Section: Discussionmentioning
confidence: 99%